Prevalence of tuberculous infection and incidence of tuberculosis: a re-assessment of the Styblo rule - F van Leth; MJ van der Werf; MW Borgdorff (The World Health Organization, 2008)
OBJECTIVE: To evaluate the validity of the fixed mathematical relationship between the annual risk of tuberculous infection (ARTI), the prevalence of smear-positive tuberculosis (TB) and the incidence of smear-positive TB specified as the Styblo rule, which TB control programmes use to estimate the incidence of TB disease at a population level and the case detection rate. METHODS: Population-based tuberculin surveys and surveys on prevalence of smear-positive TB since 1975 were identified through a literature search. For these surveys, the ratio between the number of tuberculous infections (based on ARTI estimates) and the number of smear-positive TB cases was calculated and compared to the ratio of 8 to 12 tuberculous infections per prevalent smear- positive TB case as part of the Styblo rule. FINDINGS: Three countries had national population-based data on both ARTI and prevalence of smear-positive TB for more than one point in time. In China the ratio ranged from 3.4 to 5.8, in the Philippines from 2.6 to 4.4, and in the Republic of Korea, from 3.2 to 4.7. All ratios were markedly lower than the ratio that is part of the Styblo rule. CONCLUSION: According to recent country data, there are typically fewer than 8 to 12 tuberculous infections per prevalent smear-positive TB case, and it remains unclear whether this ratio varies significantly among countries. The decrease in the ratio compared to the Styblo rule probably relates to improvements in the prompt treatment of TB disease (by national TB programmes). A change in the number of tuberculous infections per prevalent smear-positive TB case in population-based surveys makes the assumed fixed mathematical relationship between ARTI and incidence of smear-positive TB no longer valid.